Positive Thinking and Affirmative behavior and their Correlation with the Psychological Flow of Students of the Faculty of Physical Education and Sports Sciences - Yasmin Hamid Majid Al Bayati (Journal of Global Pharma Technology, 2019)
The study objectives to:To identify positive thinking, affirmative behavior and psychological flow among students of the Faculty of Physical Education and Sports sciences at the University of Babylon.To learn about the relationship between positive thinking, affirmative behavior and the psychological flow of students at the Faculty of Physical Education and Sports sciences at the University of Babylon.Researchers used the survey methodology to identify these variables, and in the relational relationship method to identify the relationship between them, the research community included the first-stage students at the Faculty of Physical Education and Sports Sciences of Babylon University for the 2017-2018 school year, which number (130) students, Thirty students from the research community were selected (25 students per college) (23.07%) The measurements were then applied for the purpose of the relations, and the appropriate statistical methods were used in the processing of the data, as the authors used the statistical pouch (SPSS).In the light of the results of the present research, and of the interpretations that have been followed, we can draw some conclusions, the most important of which are the following:First-stage students at the Faculty of Physical Education and sports sciences have positive thinking, affirmative behavior and good psychological flow.There is a strong correlation between both positive thinking and affirmative behavior on the one hand and psychological flow on the other.In the light of the findings and conclusions of the research, the current research has reached the most important recommendations, as follows:To pay attention to the psychological aspects of the students of the Faculty of Physical Education and sports sciences, in particular positive thinking and affirmative behavior, because of their direct relationship with the psychological flow;Conducting studies similar to psychological variables to determine their relationship with the basic skills of the various sporting events for students.The need to provide specific lectures to students during educational and teaching units by a psychologist and a psychologist.Keywords: Positive thinking, Affirmative behavior, Psychological flow and Sports Sciences.